A Putative ABC Transporter Permease Is Necessary for Resistance to Acidified Nitrite and EDTA in Pseudomonas aeruginosa under Aerobic and Anaerobic Planktonic and Biofilm Conditions - McDaniel, Cameron; Su, Shengchang; Panmanee, Warunya; Lau, Gee W.; Browne, Tristan; Cox, Kevin; Paul, Andrew T.; Ko, Seung-Hyun B.; Mortensen, Joel E.; Lam, Joseph S.; Muruve, Daniel A.; Hassett, Daniel J. (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa (PA) is an important airway pathogen of cystic fibrosis and chronic obstructive disease patients. Multiply drug resistant PA is becoming increasing prevalent and new strategies are needed to combat such insidious organisms. We have previously shown that a mucoid, mucA22 mutant PA is exquisitely sensitive to acidified nitrite (A-NO2-, pH 6.5) at concentrations that are well tolerated in humans. Here, we used a transposon mutagenesis approach to identify PA mutants that are hypersensitive to A-NO2-. Among greater than 10,000 mutants screened, we focused on PA4455, in which the transposon was found to disrupt the production of a putative cytoplasmic membrane-spanning ABC transporter permease. The PA4455 mutant was not only highly sensitive to A-NO2-, but also the membrane perturbing agent, EDTA and the antibiotics doxycycline, tigecycline, colistin and chloramphenicol, respectively. Treatment of bacteria with A-NO2- plus EDTA, however, had the most dramatic and synergistic effect, with virtually all bacteria killed by 25 mM (aerobic), 15 mM (anaerobic) A-NO2- and EDTA (1 mM, aerobic, anaerobic), respectively. Most importantly, the PA4455 mutant was also sensitive to A-NO2- in biofilms. A-NO2- sensitivity and an anaerobic growth defect was also noted in two mutants (rmlC and wbpM) that are defective in B-band LPS synthesis, potentially indicating a membrane defect in the PA4455 mutant. Finally, this study describes a gene, PA4455, that when mutated, allows for dramatic sensitivity to the potential therapeutic agent, A-NO2- as well as EDTA. Furthermore, the synergy between the two compounds could offer future benefits against antibiotic resistant PA strains.